Children's Guided Participation in Jazz Improvisation A Study of the 'Improbasen' Learning Centre - Johansen, Guro Gravem (London : Routledge, 2020)
Improbasen is a Norwegian private learning centre that offers beginner's instrumental tuition within jazz improvisation for children between the ages of 7 and 15. This book springs out of a two-year ethnographic study of the teaching and learning activity at Improbasen, highlighting features from the micro-interactions within the lessons, the organisation of Improbasen, and its international activity. Music teachers, students, and scholars within music education as well as jazz research will benefit from the perspectives presented in the book, which shows how children systematically acquire tools for improvisation and shared codes for interplay. Through a process of guided participation in jazz culture, even very young children are empowered to take part in a global, creative musical practice with improvisation as an educational core. This book critically engages in current discussions about jazz pedagogy, inclusion and gender equity, beginning instrumental tuition, creativity, and authenticity in childhood.
OCLC-licensed vendor bibliographic record.
Keywords: Improvisation (Music); Jazz -- Instruction and study -- Norway; MUSIC / General